Implementasi LKPD Berbasis PhET pada Materi Hukum Ohm di SMA Islam Plus Musthofa Kamal - Bq. Roswin Tiarti Sari; Nayumi Warta Nabila; Khalila Humairo Ramadhani (Indonesian Publication Center, 2026)
Physics learning on Ohm’s Law material still faces challenges in understanding abstract concepts and limitations in conducting practical activities at school. This community service activity aimed to implement PhET simulation-based student worksheets (LKPD) on Ohm’s Law material at SMA Islam Plus Musthofa Kamal as a more interactive and contextual learning alternative. The activity involved 24 eleventh-grade (Grade XI) students. The implementation method consisted of preparation, implementation, and evaluation stages. During the implementation stage, the PhET simulation was displayed using a laptop and projector because students were not allowed to bring mobile phones to school. Students observed the relationship between voltage, electric current, and resistance through the prepared worksheets and were also given the opportunity to directly try the simulation in front of the class. The results showed that the use of PhET-based worksheets increased students’ participation and enthusiasm during the learning process. Students became more active in discussions, observing experiments, and understanding the relationship between voltage, electric current, and resistance according to the concept of Ohm’s Law. Therefore, the implementation of PhET-based worksheets can be used as an effective and engaging alternative physics learning media to support classroom learning.